On the Evolution of the Great Lakes Water Quality Agreement: From Pathological Management to Adaptive Governance? Sketches of Learning From Experience - McLaughlin, Chris (My University, 2011)
The increasing interest in adaptive models of governance and adaptive tools for management stems from a recognition that the traditional paradigm in natural resource management is failing to adequately maintain the resilience of social-ecological systems. A principal reason for this failure is that each problem is treated discretely by approaches that are characteristically narrow and reactive rather than comprehensive and forward-looking. This lack of sophistication means that traditional governance models are unsuitable for dealing with the inherent uncertainty characteristic of environmental problems, and for dealing with the conflicts that emanate from the social construction of those problems. The challenge presented by these uncertainties and conflicts illuminates deficiencies in how we conceptualize the dynamics of social-ecological systems and how we formulate approaches to policy and problem solving to cope effectively with those dynamics. What changes in governance could remedy these deficiencies with more effective forms of collective action that sustain and enhance social-ecological resilience? My purpose was to pursue those changes with an examination of the human dimension of governance, with specific reference to the Great Lakes and potential features of an adaptive paradigm for the Great Lakes Water Quality Agreement. The goals of this research were to contribute knowledge and perspective on our understanding of and progress towards adaptive Great Lakes governance, and secondly, to generate pragmatic and actionable policy options for enhancing participatory processes, social learning, and leadership for adaptive Great Lakes governance. To achieve these goals, I sought the following specific objectives: (1) identify aspects of the Agreement that would compel a more rigorous and evaluative approach to policy development and implementation in the Great Lakes; (2) acquire evidence to characterize deficits in the implementation of Great Lakes policy; (3) acquire evidence to characterize pathologies in the management of the Great Lakes; (4) (i) identify, detail, and combine the principles and processes of adaptive management and decision analysis, (ii) relate these mechanisms to policy and research in the Great Lakes context, especially where such mechanisms for managing in the face of uncertainty could ameliorate implementation deficits and management pathologies; and (5) (i) acquire evidence of the strengths and limitations in the development and implementation of Great Lakes Remedial Action Plans from people with direct experience with RAPs, (ii) identify and characterize potential reforms that could improve the design of community-based, nearshore restoration programs, and (iii) measure the desirability, feasibility, and likelihood for success of those reforms. Language in the Purpose of the Agreement, that the federal governments are to develop programs and practices for a better understanding of the Great Lakes, I interpret as inviting even demanding-the ongoing and rigorous pursuit of new knowledge and improved processes in Great Lakes governance to further place-based and regional restoration. Policy implementation deficits identified included a lack of understanding of cause and effect, inadequate communication and coordination, lack of time and resources for full implementation, and lack of agreement on objectives. Pathologies of management included a lack of responsiveness, a lack of institutional analysis and program evaluation, a resistance to new information and ideas, a lack of appropriate personalities in key roles, and multiple and incompatible programming. Policy tools for improved human-environment and science-policy linkages were examined as potential governance mechanisms to counter deficits and pathologies. Design principals of adaptive management and decision analysis were specified. These tools were placed within the policy and research context of the Great Lakes regime and linked to improved forms of accountability. A three-round online Policy Delphi study involved several dozen experts in the development and implementation of RAPs across the Great Lakes basin within government, industry, academia, and civil society. The research collected and aggregated (1) direct knowledge of the strengths and limitations of RAPs, which lead to (2) further knowledge of what worked and what did not work in the RAP program, which in turn facilitated (3) the emergence of seven governance options to improve institutional processes in RAP programming. Importantly, the results establish that both the structure and attributes of governance were significant to RAP outcomes. Ran kings of these options indicated a general consensus that the options were relatively feasible and likely to succeed as enhancements in the development and implementation of RAPs. The results indicate a need to focus significantly on the predominant tendencies and characteristic attitudes that underlie RAP processes. These findings will have broad significance for other evolving place-based nearshore restoration strategies in the Great Lakes and anywhere else such programs are initiated. The thesis culminates with a conceptual framework for adaptive governance, problem solving, decision making, and management. The framework encompasses three domains that correspond to established levels of institutional analysis: constitutional choice (political and societal processes), collective choice (policy and decision processes), and operational choice (resource use and management processes). Flows of information between domains can be facilitated or restricted depending on the rules and conventions of the institutional design. Traditional governance characteristically permits only a linear and downward flow of information that negates the possibility for double-loop learning by disallowing required feedbacks. Adaptive governance regimes intentionally encourage a return or upward (and outward) flow of information and promotes learning. The three domains in the framework are nested to indicate that the 'problem domain' is the entire social system, that problems of environmental governance cannot be restricted to subsets of issues, and that adaptive problem solving is multi-scalar. The framework explicitly links processes across domains and is adaptive because it bridges boundaries that traditionally separate society from policy decisions and isolate policy decisions from management activity. The Discussion underscores that learning is a key function of adaptive governance, and that it is operationalized through social capital, networks, leadership, and trust. The thesis recommends that the federal governments issue a reference to the International Joint Commission to establish an Adaptive Governance Task Force in order to provide a strong and independent forum to engage with the conceptual framework presented in this thesis and generally to discover adequate and appropriate strategies and opportunities for adaptive Great Lakes governance.
Keywords: evolution; great lakes; water quality; adaptive governance